An approach to determining anthocyanin synthesis enzyme gene expression in an evolutionary context: an example from Erica plukenetii - Le Maitre, N C (Ann Bot, 2019)
BACKGROUND AND AIMS: Floral colour in angiosperms can be controlled by variations in the expression of the genes of the anthocyanin pathway. Floral colour shifts influence pollinator specificity. Multiple shifts in floral colour occurred in the diversification of the genus Erica (Ericaceae), from plesiomorphic pink to, for example, red or white flowers. Variation in anthocyanin gene expression and its effects on floral colour in the red-, pink- and white-flowered Erica plukenetii species complex was investigated. METHODS: Next generation sequencing, reverse transcriptase PCR and real-time reverse transcriptase quantitative PCR were used to quantify anthocyanin gene expression. KEY RESULTS: Non-homologous mutations causing loss of expression of single genes were found, indicating that the cause was likely to be mutations in transcription factor binding sites upstream of the 5′-untranslated region of the genes, and this was confirmed by sequencing. CONCLUSIONS: Independent evolution and subsequent loss of expression of anthocyanin genes may have influenced diversification in the E. plukenetii species complex. The approach developed here should find more general application in studies on the role of floral colour shifts in diversification.